2012
DOI: 10.1111/j.1471-4159.2012.07665.x
|View full text |Cite
|
Sign up to set email alerts
|

Kainate receptor‐mediated depression of glutamatergic transmission involving protein kinase A in the lateral amygdala

Abstract: The amygdala is a component of the limbic system that is involved in emotional modulation of behaviour and learning and memory (LeDoux 2000). This structure is central for the acquisition, storage, and expression of conditioned fear memory (Lavond et al. 1993;LeDoux 1996;Davis 1997;McKernan and Shinnick-Gallagher 1997;Rogan et al. 1997;Fendt and Fanselow 1999). Synaptic inputs to the lateral nucleus of the amygdala (LA) from the thalamic medial geniculate nucleus (MGN) and from the auditory cortex are essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Biophysical studies with single-channel recording have shown GluK1 activity [85], suggesting these KARs are Ca 2+ permeable. A biphasic action of KARs, activated by the agonist domoate, has been shown previously at PF-PuC synapse, with low agonist concentrations, facilitating synaptic transmission and higher concentrations depressing synaptic transmission [86] in agreement with what has been found in the hippocampus [87][88][89], cortex [90], amygdala [91], and the thalamus [92]. EPSC trial-to-trial fluctuation analysis, failure rates, as well as paired-pulse ratios have shown that these facilitatory and depressive actions of KARs in the cerebellum are mediated by presynaptic KARs [80].…”
Section: Kars Modulating Glutamate Release In the Cerebellum: A Biphasupporting
confidence: 86%
See 1 more Smart Citation
“…Biophysical studies with single-channel recording have shown GluK1 activity [85], suggesting these KARs are Ca 2+ permeable. A biphasic action of KARs, activated by the agonist domoate, has been shown previously at PF-PuC synapse, with low agonist concentrations, facilitating synaptic transmission and higher concentrations depressing synaptic transmission [86] in agreement with what has been found in the hippocampus [87][88][89], cortex [90], amygdala [91], and the thalamus [92]. EPSC trial-to-trial fluctuation analysis, failure rates, as well as paired-pulse ratios have shown that these facilitatory and depressive actions of KARs in the cerebellum are mediated by presynaptic KARs [80].…”
Section: Kars Modulating Glutamate Release In the Cerebellum: A Biphasupporting
confidence: 86%
“…Kainate Receptors Modulating Glutamate Release in the Cerebellum DOI: http://dx.doi.org /10.5772/intechopen.87984 was observed as reported for other different brain areas including thalamus, cortex, hippocampus, and amygdala [89][90][91][92]. This depression of glutamate release was prevented in the presence of cAMP-RP (which inhibits the activation of PKA), but was not affected by any other experimental modification discussed above with respect to the facilitation of glutamate release.…”
Section: Action Mechanism For Kars-mediated Depression Of Glutamate Rsupporting
confidence: 72%
“…As in the hippocampus, facilitatory (Shin et al, 2010 ) and inhibitory (Negrete-Díaz et al, 2012 ) effects on glutamate release mediated by KAR activation have been described. A presynaptic AC/cAMP/PKA cascade mediating the depression of glutamate release through activation of presynaptic KARs has been shown at medial geniculate nucleus (MGN)-amygdala nucleus (LA) synapses (Negrete-Díaz et al, 2012 ). The effect was prevented by block of cAMP/PKA signaling by both Rp-Br-cAMP and H-89, but not by calphostin C inhibition of PKC.…”
Section: Amygdalamentioning
confidence: 99%
“…Similarly, biphasic modulation is also evident in the modulation of glutamate release by KARs. Thus, KARs invoke both inhibitory effects (Vignes et al, 1998 ; Contractor et al, 2000 , 2003 ; Kamiya and Ozawa, 2000 ; Schmitz et al, 2000 ; Negrete-Díaz et al, 2006 , 2007 , 2012 ; Lyon et al, 2011 ), and facilitatory modulation of glutamate release (Bortolotto et al, 1999 ; Contractor et al, 2001 , 2003 ; Lauri et al, 2001a , b ; Breustedt and Schmitz, 2004 ; Rodríguez-Moreno and Sihra, 2004 , 2013 ; Pinheiro et al, 2007 ; Scott et al, 2008 ; Fernandes et al, 2009 ; Andrade-Talavera et al, 2012 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro slice recording showed that GluK1 is selectively expressed in interneurons, and its activation could largely depolarize those interneurons and increase synaptic GABA release as well as GABA tonic currents. More importantly, the GluK1 activation in the basolateral amygdala reduced the output to the central amygdala, which may explain the increased anxiety phenotype in the GluK1 knockout mice [6] In addition, the regulation of excitatory glutamate transmission by KA receptors have been also reported in the amygdala [30, 31], and such regulation is also mixed (inhibition and facilitation).…”
Section: Ka Receptor and Synaptic Regulationmentioning
confidence: 99%